Observations from the U.S. Federal Income Tax to Distinguish Between Measures of Progressivity and Redistributive Capacity - Timoty Mathews (Central European Public Administration Review)
This study provides insights on the attributes of a tax that are measured by two different classes of progressivity indices – those defined by Kakwani (1977), Suits (1977), Stroup (2005), and Mathews (2016) and those defined by Musgrave & Thin (1948) and Reynolds & Smolensky (1977). Index values are determined for the U.S. Federal Income Tax from 1929 through 2010. These values illustrate that the indices of Kakwani, Suits, Stroup, and Mathews gauge the progressivity of the tax, while those of Musgrave & Thin and Reynolds & Smolensky measure the redistributive capacity of the tax. In the early 1940s the progressivity of this tax significantly decreased at the same time when the redistributive capacity of the tax significantly increased. Since the mid-1970s this tax has (i) been more progressive than it was from the early 1950s through the mid-1970s and (ii) redistributed income to a greater degree than it did from the early 1950s through the mid-1970s.